2022
DOI: 10.1002/nafm.10748
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Spatiotemporal Variation in Survival of Endangered Winter‐Run Chinook Salmon Out‐migrating from the Sacramento River

Abstract: Among four extant and declining runs of Chinook Salmon Oncorhynchus tshawytscha in California's Central Valley, none has declined as precipitously as the Sacramento River winter run. Migratory winter-run Chinook Salmon employ a life history strategy to reside and feed in stopover habitats on their way from freshwaters to the ocean. Migratory winter run, on their way from freshwaters to the ocean, employ a life history strategy to reside and feed in stopover habitats that have been affected by anthropogenic dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 76 publications
(113 reference statements)
2
13
0
Order By: Relevance
“…This work will provide managers and modelers with a better understanding of the degree to which different habitats and temperature affect growth. Furthermore, these growth models can be integrated within lifecycle models to test hypotheses of how different size‐specific survival rates (Hassrick, Ammann, Perry, John, & Daniels, 2022; Perry et al, 2018) could affect long‐term population dynamics, ultimately informing efforts to recover threatened and endangered populations of Chinook salmon.…”
Section: Discussionmentioning
confidence: 99%
“…This work will provide managers and modelers with a better understanding of the degree to which different habitats and temperature affect growth. Furthermore, these growth models can be integrated within lifecycle models to test hypotheses of how different size‐specific survival rates (Hassrick, Ammann, Perry, John, & Daniels, 2022; Perry et al, 2018) could affect long‐term population dynamics, ultimately informing efforts to recover threatened and endangered populations of Chinook salmon.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous environmental factors have been hypothesized to influence the distribution of juvenile winter-run salmon in the Estuary. Previous studies have demonstrated relationships between juvenile salmon occupancy or abundance and flow characteristics, water clarity and temperature, weather, upstream juvenile production and distribution, and time (Brandes and McLain 2001;Sommer et al 2005;del Rosario et al 2013;Acierto et al 2014;Perry et al 2016;Hassrick et al 2022). However, few studies (e.g., del Rosario et al 2013;Hassrick et al 2022) have directly evaluated the influence of these factors on juvenile winter-run salmon occupancy, and no studies have accounted for sampling uncertainties, including imperfect detection and misidentification during their evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…We obtained readily available data representing water quality and other environmental characteristics that were hypothesized to influence juvenile winter-run salmon occupancy and detection near Sacramento (Table 1; Brandes and McLain 2001;Sommer et al 2005;del Rosario et al 2013;Acierto et al 2014;Hassrick et al 2022). Water temperature was measured by DJFMP staff to the nearest 0.1°C approximately 0.5 m below the water surface by using a nonmercury thermometer, a YSI Model 85 meter, or a YSI PRO 2030 meter during or immediately before each Sacramento trawl tow and beach seine haul.…”
Section: Environmental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Red Bluff represents the end of the migratory corridor for adult salmon on the Sacramento, and the beginning of the migratory corridor for juvenile salmon that are born upstream, and so exposure time to potentially warm water temperatures downstream of here is a function of migration rates. Limited adult Chinook salmon telemetry data has shown travel times of 10–45 days to transit the non‐tidal lower Sacramento River before arriving to Red Bluff (Martin et al., 2015), and actively migrating juvenile Chinook salmon can take of 3–60 days to reach the tidal portions of the river after leaving Red Bluff (Hassrick et al., 2022; Michel et al., 2013).…”
Section: Methodsmentioning
confidence: 99%